2022
DOI: 10.3389/fpsyt.2022.922360
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Training Intervention With the Persian Version of the Mindfulness Training Mobile App for Premenstrual Syndrome: A Randomized Controlled Trial

Abstract: Premenstrual syndrome (PMS) is a common problem for women of reproductive age, affecting various aspects of their lives. While various in-person psychotherapeutic interventions, including Mindfulness therapy, have yielded promising results in reducing PMS symptoms, due to the COVID-19 Pandemic, psychotherapists are providing their services via online methods. Therefore, the present study is the first one worldwide to examine whether smartphone-based Mindfulness training can reduce symptoms of PMS and improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…These findings are consistent with other studies in which PMSS levels declined in students after an MBSR program intervention. 23,31,32 A controlled clinical trial (n = 30) 8session cognitive disease-based mindfulness therapy reduced PMS symptoms and anxiety in university students through 3 months follow-up. 31 In a similar small controlled trial (n = 30), Shabani and Khalatbari found that 8-session MBSR increased psychological well-being and improved emotion regulation in women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with other studies in which PMSS levels declined in students after an MBSR program intervention. 23,31,32 A controlled clinical trial (n = 30) 8session cognitive disease-based mindfulness therapy reduced PMS symptoms and anxiety in university students through 3 months follow-up. 31 In a similar small controlled trial (n = 30), Shabani and Khalatbari found that 8-session MBSR increased psychological well-being and improved emotion regulation in women.…”
Section: Discussionmentioning
confidence: 99%
“…A Mindfulness Training mobile app reduced the psychological, physical, and behavioral symptoms related to PMS and increased the quality of life of women in a controlled trial of 80 women between 25 and 40 years of age. 32 Similarly, mindfulness-based cognitive-behavioral therapy has also been found to be effective in reducing PMS symptoms. 1,33 Mindfulness practices can beneficially affect the mind, autonomic nervous system, stress, immune system, and physical condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-medical therapies generally include alimentary therapeutics [ 14 , 15 ] as well as complementary and alternative medicine such as rest, heat compress, traditional Chinese medicine, lifestyle changes, meditation, regular exercise, etc. [ 16 , 17 , 18 , 19 ], which are commonly used. Many recent studies have discussed the effect of exercise on premenstrual symptoms [ 20 , 21 , 22 ], mainly because it is not only convenient, non-invasive, and has low side effects but also maintains overall health.…”
Section: Introductionmentioning
confidence: 99%